DAMPAK LOAN TO DEPOSIT RATIO (LDR) DAN NON PERFOMING LOAN (NPL) TERHADAP PERTUMBUHAN HARGA SAHAM PADA BANK BUMN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wahyu, Didin Rasyidin; Yuliah, Yuliah; Fahreza, Lisa Ananda (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
The state-owned banking sector faces challenges such as fluctuating financial performance, fluctuating stock prices, and adequate capital needs. This creates uncertainty among investors and requires effective strategies to improve the company's performance and value in the face of fierce competition. This study aims to determine the Effect of Loan to Deposit Ratio (LDR) and Non-Perfoming Loan (NPL) on Stock Price Growth in Conventional SOEs Banks listed on the Indonesia Stock Exchange for the 2015-2023 period. The population in this study is Conventional State-Owned Banking Companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2023 period. The sample in this study is 4 Conventional SOE banking companies with a research time of 9 years so that 36 samples obtained by Saturated Sampling Technique are produced. The results of this study are that the Loan to Deposit Ratio (LDR) and Non-Perfoming Loan (NPL) have a simultaneous effect. Partially, the Loan to Deposit Ratio (LDR) has no effect and NonPerforming Loans (NPL) have a negative effect on stock price growth